“Deep” Time in Times of Precarity. Comics and Anthropocene Poetics - Rommens, Aarnoud (Captures)

(untitled) (Figura, Centre de recherche sur le texte et l'imaginaire, 2019)
This essay focuses on comics that show a sensitivity to “deep time” and the conception of our current epoch as the so-called “Anthropocene”. Through comics by Diniz Conefrey, Alberto Breccia and the WREK collective, this text explores how the bodily temporality of reading and drawing stands in productive counterpoint to some of the themes of these comics. These thematic layers are informed by the interpretive horizon of geological time and pose a politics of form to negotiate this contradiction.